pre calc

(cos3x)^2+(sin3x)^2=cos(f(x))

find f(x)

  1. 👍 0
  2. 👎 0
  3. 👁 68
asked by dylan
  1. cos anything^2 + sin same thing^2 = 1
    so cos (f(x)) = 1
    f(x) = 0 or 360 or 720 .........

    1. 👍 0
    2. 👎 0
    posted by Damon
  2. Hey, Steve already answered that for you.

    1. 👍 0
    2. 👎 0
    posted by Damon

Respond to this Question

First Name

Your Response

Similar Questions

  1. precalc

    (cos3x)^4+(sin3x)^4=cos(g(x)) find g(x)

    asked by dylan on April 21, 2013
  2. precalc

    (cos3x)^4+(sin3x)^4=cos(g(x)) find g(x)

    asked by dylan on April 21, 2013
  3. precalc

    (cos3x)^4+(sin3x)^4=cos(g(x)) find g(x)

    asked by dylan on April 21, 2013
  4. maths

    prove that cos3x+sin3x/cos x-sin x=1+2sin2x

    asked by sunny on July 22, 2009
  5. Maths

    given (e^x)sin3x = Im((e^x)(e^i3x)) Integrate (e^x)sin3x.dx You can just take the imaginary part of the integral of ((e^x)(e^i3x))= e^([3i +1)x] which is IM(3i +1)e^(3ix + x) = IM (3i +1)e^x*e^(3ix) = IM {(3i +1)*e^x* [ cos (3x) +

    asked by Tom on January 20, 2007
  6. Calculus part 3 so sorry

    y = e^2xsin3x Find the derivative. So I used the product rule and I got sin3x(e^2x)+cos^3x(e^2x). But the actual answer is sin3x(2e^2x)+cos^3x(3e^2x) Where the the 2 and 3 before the e come from?

    asked by Samantha on November 4, 2008
  7. math

    Solve sin2x + sin4x = cos2x + cos 4x for x in the interval[0,2pi) Hint: the following substitution should come in handy: sin3x= cos3x . tan3x

    asked by greg on December 3, 2012
  8. maths

    If (e^x)(sin3x)=Im ((e^x)(e^i3x)) integrate (e^x)(sin3x) I get the answer(e^x)(cos3x-3sin3x) +C My book gets the answer (1/10)(e^x)(sin3x-3cos3x)+C Can any explain which answer is right and why Integral of e^(1+3i)x = e^(1+3i)x

    asked by Tom on January 20, 2007
  9. maths

    Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic factors; deduce that cos3x = 4[cos(x) -cos(pi/6)][(cos(x) -cos(pi/2)][(cos(x) -cos(5pi/6)]

    asked by jake on November 10, 2008
  10. maths

    Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic factors; deduce that cos3x = 4[cos(x) -cos(pi/6)][(cos(x) -cos(pi/2)][(cos(x) -cos(5pi/6)]

    asked by jake on November 10, 2008

More Similar Questions